PENGARUH BUDAYA KERJA DAN TIM KERJA TERHADAP KINERJA KARYAWAN PADA PT. PLN (PERSERO) UNIT LAYANAN PELANGGAN MUARA ENIM - Yuli Anita; Zubaidah Warni; Kardiyanto Kardiyanto (TECHNOBIZ : International Journal of Business, 2025)
Performance is the result of employee work in terms of quality, quantity, working time, and cooperation to achieve the objectives set by the organization. One of the factors that influence performance is Work Culture and Work Team. This study discusses the influence of work culture and work team on employee performance at PT PLN (PEESERO) Muara Enim Customer Service Unit. This study is an associative study that seeks to find the relationship between one variable and another variable. The population in this study was all employees of PT. PLN (Persero) Muara Enim Customer Service Unit, totaling 111. The sample used was a saturated sample using the entire population. The results of the study show that there is a positive and significant influence between work culture and teamwork on employee performance. The regression coefficient value f count (163.491) > f table (3.20). Thus, the null hypothesis Ho, which states that work culture and teamwork have a positive and significant effect on employee performance at PT. PLN (Persero) Muara Enim Customer Service Unit, can be accepted. The results of the coefficient of determination test, r2, are 0.874, meaning that the percentage contribution of the work culture and work team variables to performance is 87.4%, while the remaining 12.6% is influenced by other variables not included in this study.